Memory CD8 T Cells Specific for Plasmodia Liver-Stage Antigens Maintain Protracted Protection Against Malaria - Krzych, Urszula; Dalai, Sarat; Zarling, Stasya N.; Pichugin, Alexander V. (Frontiers in Immunology, 2012)
Immunologic memory induced by pathogenic agents or vaccinations is inextricably linked to long-lasting protection. Adequately maintained memory T and B cell pools assure a fast, effective and specific response against re-infections. Studies of immune responses amongst residents of malaria endemic areas suggest that memory responses to Plasmodia antigens appear to be neither adequately developed nor maintained, because persons who survive episodes of childhood malaria remain vulnerable to persistent or intermittent malaria infections. By contrast, multiple exposures of humans and laboratory rodents to radiation-attenuated Plasmodia sporozoites (γ-spz) induces sterile and long-lasting protection against experimental sporozoite challenge. Protection is associated with MHC class I-dependent CD8 T cells, the key effectors against pre-erythrocytic stage infection. We have adopted the P. berghei γ-spz mouse model to study memory CD8 T cells that are specific for antigens expressed by Pb liver-stage (LS) parasites and are found predominantly in the liver. On the basis of phenotypic and functional characteristics, we have demonstrated that liver CD8 T cells form two subsets: CD44hiCD62LloKLRG-1+CD107+CD127-CD122loCD8 T effector/effector memory (TE/EM) cells that are the dominant IFN-γ producers and CD44hiCD62LhiKLRG-1-CD107-CD127+CD122hiCD8 T central memory (TCM) cells. In this review, we discuss our observations concerning the role of CD8 TE/EM and CD8 TCM cells in the maintenance of protracted protective immunity against experimental malaria infection. Finally, we present a hypothesis consistent with a model whereby intrahepatic CD8 TCM cells, that are maintained in part by LS-Ag depot and by IL-15-mediated survival and homeostatic proliferation, form a reservoir of cells ready for conscription to CD8 TE/EM cells needed to prevent re-infections.